CAPACITAÇÃO DOCENTE PARA EAD Um estudo sobre a capacitação que o docente do ensino superior recebe para atuar na educação a distância. - Friedrich, Giovana Quini (2013)
In Higher Education, one of the current discussions is offering undergraduate and postgraduate in the distance. Given the present discussion that occurs around the Distance Education - Distance Education, this study aimed to identify the training that the teacher who prepares and teaches the class receives the institution in which it operates, with a view that is one of the main actors this scenario. The literature and documents, showed the current scenario of Distance Education, current regulations and especially the positions for and against this discussion. It is noticeable that even facing difficulties, distance education has shown rapid growth in recent years. Be on the number of courses offered, or the number of students enrolled in distance education has taken space in Higher Education. The focus of this research is the faculty engaged in distance learning and to investigate the training that teachers receive, the second time of the survey, questionnaires were offered to teachers working in EAD and interviews with professionals who design and plan the training for these teachers. From the questionnaires performed an analysis of the aspects considered essential by teachers. This analysis prioritized the aspects defined categories emerged where they provided, along with the interviews, designing training that is performed. It was interesting to note that the two institutions participating in the research has been very successful in developing their programs, since research carried out point as well evaluated by their students. Are institutions with different philosophies and structures, with educational projects based on different theoretical assumptions, but with models of distance education similar. As a result of this research, I noticed that the way of planning for the training of teachers, follows the philosophy and way of thinking of each of the institutions. I am aware that much remains to be done in education in our country, but the offering undergraduate courses in distance mode now shows progress and empowerment, in line with the assumptions that underlie the pedagogical project, contributes to the quality of training the egress of this modality.